Impact of primary care usual provider type and provider interdependence on outcomes for patients with diabetes: a cohort study - George L Jackson; Valerie A Smith; Sharron Docherty; Christine Everett; Jacob Christy; Heather Batchelder; Perri A Morgan; John B Anderson; Anthony Viera (BMJ Open Quality)
Background Interprofessional primary care (PC) teams are key to the provision of high-quality care. PC providers often ‘share’ patients (eg, a patient may see multiple providers in the same clinic), resulting in between-visit interdependence between providers. However, concern remains that PC provider interdependence will reduce quality of care, causing some organisations to hesitate in creating multiple provider teams. If PC provider teams are formalised, the PC usual provider of care (UPC) type (physician, nurse practitioner (NP) or physician assistant/associate (PA)) should be determined for patients with varying levels of medical complexity.Objective To evaluate the impact of PC provider interdependence, UPC type and patient complexity on diabetes-specific outcomes for adult patients with diabetes.Design Cohort study using electronic health record data from 26 PC practices in central North Carolina, USA.Participants Adult patients with diabetes (N=10 498) who received PC in 2016 and 2017.Outcome Testing for diabetes control, testing for lipid levels, mean glycated haemoglobin (HbA1c) values and mean low-density lipoprotein (LDL) values in 2017.Results Receipt of guideline recommended testing was high (72% for HbA1c and 66% for LDL testing), HbA1c values were 7.5% and LDL values were 88.5 mg/dL. When controlling for a range of patient and panel level variables, increases in PC provider interdependence were not significantly associated with diabetes-specific outcomes. Similarly, there were no significant differences in the diabetes outcomes for patients with NP/PA UPCs when compared with physicians. The number and type of a patient’s chronic conditions did impact the receipt of testing, but not average values for HbA1c and LDL.Conclusions A range of UPC types on PC multiple provider teams can deliver guideline-recommended diabetes care. However, the number and type of a patient’s chronic conditions alone impacted the receipt of testing, but not average values for HbA1c and LDL.